2017
DOI: 10.17094/ataunivbd.347970
|View full text |Cite
|
Sign up to set email alerts
|

Ratlarda Methotrexate Kaynaklı Karaciğer Toksisitesine Karşı Silymarin ve Naringin’in Yararlı Etkileri

Abstract: Öz: Karaciğer toksisitesi, kemoterapötik bir ilaç olan methotrexate (MTX) terapisinin komplikasyonlarının sonucunda oluşur. Silymarin (SLY) ve naringin (NRG) antioksidant, anti-inflamatuvar ve anti-hiperlipidemik gibi birçok farmakolojik özelliklere sahip biyoflavonoidlerdir. Bu çalışma ratlarda MTX kaynaklı karaciğer toksisitesi üzerine SLY ve NRG'in yararlı etkilerinin araştırılması için yapılmıştır. Ratlara (20 mg/kg) tek doz periton içi MTX verildikten sonra 7 gün boyunca (25 ve 50 mg/kg) SLY ve (50 ve 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Although there are many studies investigating the effects of plant extracts on healthy rats (Kandemir et al, 2017;Mercan et al, 2017;El Hendy and Al Gemeai, 2014;Oduola et al, 2010), no study has been found evaluating the effects of L. orientalis on the kidney and liver when oral administered. The most relevant study on this topic investigated the protective effects on different doses of L. orientalis oil on carbon tetrachloride (CCI4)-induced liver damage in rats, but were not evaluated effects on the livers of healthy rats (Aydýngöz et al, 2013).…”
Section: Kidneymentioning
confidence: 99%
“…Although there are many studies investigating the effects of plant extracts on healthy rats (Kandemir et al, 2017;Mercan et al, 2017;El Hendy and Al Gemeai, 2014;Oduola et al, 2010), no study has been found evaluating the effects of L. orientalis on the kidney and liver when oral administered. The most relevant study on this topic investigated the protective effects on different doses of L. orientalis oil on carbon tetrachloride (CCI4)-induced liver damage in rats, but were not evaluated effects on the livers of healthy rats (Aydýngöz et al, 2013).…”
Section: Kidneymentioning
confidence: 99%